DRiMaP--A Model of Distributed Risk Management Process - Kajko-Mattsson, M.; Sjokvist, K.; Soderstrom, J.; Krogdahl, D. (2009 Fifth International Joint Conference on INC, IMS and IDC, 2009)
Distributed software development creates many challenges to the primary contractors having the responsibility of delivering high quality products to their customers. To tackle these challenges, organizations must have an efficient distributed development process in place. They must also effectively manage risks within this distributed environment. In this paper, we suggest DRiMaP - a model of distributed risk management. This model has been designed at IBM Sweden.